Atomically flat and thermally stable graphene on Si(111) with preserved intrinsic electronic properties. Issue 18 (27th April 2018) - Li, Xiaoxia; Li, Bin; Fan, Xiaodong; Wei, Laiming; Li, Lin; Tao, Ran; Zhang, Xiaoqiang; Zhang, Hui; Zhang, Qiang; Zhu, Hongbin; Zhang, Shengbai; Zhang, Zhenyu; et al.
Abstract : Atomically flat and thermally stable graphene is achieved on the chemically active Si(111) surface, with preserved intrinsic electronic properties. Abstract : Silicon and graphene are two wonder materials, and their hybrid heterostructures are expected to be very interesting fundamentally and practically. In the present study, by adopting fast dry transfer and ultra-high vacuum annealing, atomically flat monolayer graphene is successfully prepared on the chemically active Si(111) substrate. More importantly, the graphene overlayer largely maintains its intrinsic electronic properties, as validated by the results of the energy-dependent electronic transparency, Dirac point observation and quantum coherence characteristics, and further confirmed by first-principles calculations. The intrinsic properties of graphene are retained up to 1030 K. The system of atomically flat and thermally stable graphene on a chemically active silicon surface with preserved inherent characteristics renders the graphene/silicon hybrid a promising system in the design of high-performance devices and the exploitation of interfacial topological quantum effects.